Audit Keselamatan Jalan pada Jalan Yogyakarta-Purworejo KM 35-40, Kulon Progo, Yogyakarta - Hardianto R. Mayuna, Wahyu Widodo , (Jurnal Semesta Teknika, 2012)
Among 2008 until 2010, Polsek Temon Kulon Progo recorded that there are 197 traffic accidents in arterial road which connecting Yogyakarta and Purworejo. Because of the frequent occurence of accidents at that road, it is necessary to analyze the cause of traffic accident. Â Road Safety Audit is needed to identify the highly-risky situation or the potency of accidents happened.This study used checklists and focused on the answer ânoâ and also identified the other supporting infrastructures that do not meet the standard and technical requirements. Primary data were obtained from field observations by measuring spot speed and supervising traffic facilities along the way, while the secondary data in the form of traffic accidentâs data from 2008 until 2010 were obtained from Polsek Temon. The result showed that from 2008 until 2010 at Yogyakarta-Purworejo road KM 35-40 as many as 197 events occurred with 75 person were seriously injured and another 142 people were lightly injured. The number of accident victims who died were male and the highest number of accident victims under the age of 35 years. Most accidents occured at KM 39, and in the morning (86 events). The cause of the accidents was mostly human (137 events). Pedestrians Accident is as many as 6 cases, and head-on is as many as 14 cases. It is also found that road-shoulders were still used as parking area or selling gasoline, as well as placing some flyers. The absence of special lanes for bicycles or other vehicles such as rickshaws, lack of sidewalks so that pedestrians use the road shoulder as a means of foot walking, shoulder width on the ringth and on the left of the road is not symmetrical, and also the -lack of drainage maintenance caused puddles occurs during the rainy season. Placing of power and telephone poles and lines is quite appropriate, but trees that was on the shoulder of the road still needs to be checked regularly so as not to interfere with the sight-distance of road users.